Department of Accounting, College of Administrative and Financial Sciences, Imam Ja'afar Al-Sadiq University, Baghdad, Iraq. - Saber Abood , Mseer (South Asian Journal of Social Sciences and Humanities, 2025)
This research seeks to clarify the concept of institutional corruption, which many countries  suffer from, especially various developing countries, including Iraq. It takes on multiple,  broad dimensions, intertwined with various factors, including the effectiveness of external  audit and inspection bodies. Therefore, the importance of the research lies in clarifying the  role that external audit and inspection bodies can play in eliminating institutional corruption  within the government institutions subject to their oversight, and the extent to which these  bodies adhere to regulations and laws to preserve public funds. The research yielded a set of  conclusions, the most important of which is that there is a clear role for external audit and  inspection bodies in identifying cases of institutional corruption in Iraq, but they do not report  them to the relevant anti-corruption bodies in a timely manner. Nevertheless, their absence  from performing their duties will lead to increased manipulation of public funds, violations  and breaches of financial laws, an increase in embezzlement, waste of public funds, and the  exploitation of influence and government positions. The research reached a set of  recommendations, including the need for serious work by all official and popular sectors to  lift all covers on corruption, especially technical covers. Legal and administrative measures  are needed to enable external audit and inspection bodies to combat corruption more  effectively. Proposals for draft laws criminalizing practices and actions that contribute to the  emergence and spread of corruption are also proposed, and legislative bodies are required to  approve and implement them. Managements of state institutions are selected from those with  a good reputation and professional competence, not based on criteria of proximity or distance  from influential authorities
Keywords: External audit; Inspection bodies; Institutional corruption; combating